Pattern of Skin Diseases Among Patients Visiting a Private Tertiary Care Hospital in Karachi - Sana Siddiqui; Maryam Muhammad Sharif; Feroza Fatima; Erum Ashraf (Journal of the Dow University of Health Sciences, 2022)
Objective:  To determine the pattern of skin diseases among individuals attended dermatology camp in a private tertiary care hospital in the winter season in Karachi, Pakistan.